(untitled) (Philological Studies, 2019)
A good one-language explanatory historical dictionary gives information about (loan-)words as comprehensively as possible, therefore containing etymological section as well. Information rendered within this section directs users towards searching for more detailed information about a word’s origin in etymological dictionaries. Identifying each loanword, conducted by the editors of the growing Dictionary of the 16th Century Slovene, is only possible through the comparison of that term with the initial (and not necessarily original) foreign-language word borrowed in the Slovene. The etymological explanation is also found in the dictionary articles regarding the linguistic calques. Etymological data is sometimes rendered in longer foreign-language quotes taken from the originals.